A qualitative study of public health nurses' perspectives and experiences on nutritional guidance for parents of infants and toddlers - Christine Helle; Elisabet R. Hillesund; Nina Cecilie Øverby (Maternal and Child Nutrition, 2024)
Abstract In Norway, public health nurses (PHNs) are responsible for giving parents nutritional knowledge, but limited research describes how they perceive this task. This study explores PHNs' perceptions and experiences on nutritional guidance for parents of infants and toddlers. Semistructured interviews with six PHNs were conducted and transcribed verbatim. Data were subjected to thematic analysis. Five main themes were identified: (1) Dietary guidance for parents is central to the work; (2) PHNs perceive they have parents' trust, and parents are in general open to nutrition counselling; (3) food and meals must be seen in light of the family context; (4) The dialogue must be adapted to the individual family; and (5) PHNs have expertise on nutrition; however, updating knowledge is difficult. Nutritional guidance was perceived by PHNs as a core activity. They felt that they had parents' trust, and that parents were particularly open to nutritional guidance during the first 2 years. Counselling was generally well received, but conversations on overweight were perceived as difficult. PHNs strove to tailor their guidance to individual needs. However, providing guidance on a wide range of issues in different families and cultures could be challenging. They acknowledged a need for updating knowledge but the offer of courses was sparse. Our findings suggest a discrepancy between how nutrition is prioritized in the education of PHNs and what they encounter in clinical practice. In the future, this should be given more attention given the PHNs' unique position to promote healthy eating and long‐term health.